Pendampingan Kelompok Tani Aneka Tanaman Memanfaatkan Sampah Organik dan Limbah Potong Ayam Sebagai Pupuk Organik Cair - Saronom Silaban; Murniaty Simorangkir; Choms Gary Ganda Tua Sibarani; Juniar Hutahaean; Kristin Wulan Liberti Vivanis Gulo; Litani Fivetrin Siregar; Fuaddinda Putri Salsabila; Martua Haojahan Saragih; Diana Fitri (Cv. Utility Project Solution, 2022)
Liquid organic fertilizer (POC) is a solution of fermented organic matter derived from animal waste, plant residues, and humans. Using POCs in plants stimulates the better growth of stems, leaves, fruits, and seeds. This PKM activity aims to train partners of the